REVITALISASI TEBA MODERN SEBAGAI ECO-EDUCATION SPACE PENGOLAH SAMPAH ORGANIK DI PKBM MENTARI FAJAR JIMBARAN - Komang Hari Santhi Dewi; I Nyoman Bagus Pramartha; Rifky Lana Rahardian; Christina Christina; Hafy Muhammad Sucipto; I Gede Andre Suryasa Putra; Idham Surya Firdaus (Jurnal Edukasi Pengabdian Masyarakat, 2026)
Waste management remains one of the major environmental issues requiring the active involvement of Community Learning Centers (Pusat Kegiatan Belajar Masyarakat/PKBM) through environmental-based learning. However, many PKBMs still have limited capacity to utilize available land as an environmental education medium for organic waste management. PKBM Mentari Fajar Jimbaran faced several challenges, including the underutilization of teba land as an environmental education space, the absence of digital learning media on organic waste management, and the limited product packaging design skills of learners. In response to these challenges, this community service program aimed to enhance the partner’s capacity through the revitalization of a modern teba as an eco-education space, the development of instructional videos, and product packaging design training. The program was implemented through four stages: planning, implementation, mentoring, and evaluation, involving 30 participants consisting of tutors and learners. Pre-test and post-test instruments were employed to evaluate participants’ learning outcomes. The results demonstrated that the modern teba and digital learning media for organic waste management were successfully implemented as effective learning resources. The evaluation revealed that 86% of participants achieved the very good category and 14% achieved the good category in organic waste management competencies. Furthermore, participants’ product packaging design skills improved substantially, with 68% reaching the good category and 30% the very good category after the training. Overall, the program successfully enhanced participants’ competencies in organic waste management and product packaging design.